2010
DOI: 10.1002/ar.21078
|View full text |Cite
|
Sign up to set email alerts
|

Increased COX2 in the Trigeminal Nucleus Caudalis Is Involved in Orofacial Pain Induced by Experimental Tooth Movement

Abstract: Pain is among the major problems during orthodontic treatment. Recent studies have shown that central Cyclooxygenase2 (COX2) pathway was involved in several pain models. The present study investigated whether inducible COX2 within the trigeminal nucleus caudalis (Vc) contributed to experimental tooth movement pain in freely moving rats. Elastic rubber bands were inserted between the first and second maxillary molars bilaterally to establish tooth movement model. The directed mouth wiping behavior was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…In accordance with the present finding, Gao & Duan () indicated that the expression of COX‐2 in Vc is up‐regulated following experimental tooth movement inflammation. Moreover, central COX‐2 inhibition decreases temporomandibular joint inflammation induced by formalin in rats (Ahn et al .…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with the present finding, Gao & Duan () indicated that the expression of COX‐2 in Vc is up‐regulated following experimental tooth movement inflammation. Moreover, central COX‐2 inhibition decreases temporomandibular joint inflammation induced by formalin in rats (Ahn et al .…”
Section: Discussionsupporting
confidence: 92%
“…In the central nervous system, COX-2 is highly distributed in hippocampal neurons and its expression is correlated with the induction of pro-inflammatory cytokines and pain molecules 21 . In the study by Gao and Duan, increased COX-2 in the trigeminal subnucleus caudalis of rats was observed following tooth movement pain 5 . Capsaicin activates transient receptor potential vanilloid 1 channels on a subpopulation of primary afferent sensory neurons, specifically C fibers, involved in nociception.…”
Section: Discussionmentioning
confidence: 95%
“…Most patients undergoing orthodontic treatment experience pain and discomfort, not only from teeth, but also from other areas, such as the cheek and masseter muscle , which spreads as referred pain. Despite its detrimental impact on patients, little is known about the underlying mechanism of this referred pain in orthodontic patients, which makes prevention procedurally more difficult . Tooth‐movement pain has been attributed to associated pressure, ischemia, inflammation, and edema , all of which can lead to the release of inflammatory mediators, such as prostaglandin E 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Tooth‐movement pain has been attributed to associated pressure, ischemia, inflammation, and edema , all of which can lead to the release of inflammatory mediators, such as prostaglandin E 2 . Recently, using an experimental tooth‐movement model in rats, Gao & Duan demonstrated that tooth‐movement pain involved increased COX‐2 in the SpVc, but not in the periodontal tissue, suggesting that central COX‐2 inhibition holds therapeutic promise in the treatment of orofacial pain induced by orthodontic tooth movement. It can be postulated that lutein administration attenuates mechanical hyperalgesia and this effect is mainly a result of the suppression of excitability of SpVc WDR neurons via inhibition of the COX‐2 signaling cascade pathway.…”
Section: Discussionmentioning
confidence: 99%